Toxicity profiles between strains of Alexandrium tamiyavanichii - Hamdan, Nurul Ashima; Abu Hassan, Muhamad Shafiq; Muhamad Bunnori, Noraslinda (2016)
Phycotoxins are byproducts of toxic microalga that capable of causing severity on hu-mans upon consuming contaminated seafood. The threshold level for bivalve toxicity accumulation has been universally compromised by the scientist worldwide to be 80μg/STX equivalent. The amount of toxins released by microalgae however varies according to species as some of the microalgae synthesize toxins within small number of cells while others required a blooming event for the toxins to be detected. It is also possible for the toxicity of one species being gradually decreases throughout years in culture. Alexandrium tamiyavanichii has been reported to cause toxicity in seafood products that subject to hospitalized cases in Malaysia. Genus Alexandrium has been known for the stability of the saxitoxin production yet no total loss of toxicity has been recorded. Two cultures of A. tamiyavanichii have been tested for its toxicity using high-performance liquid chromatography (HPLC) with GTX standards as the reference. Strains isolated from Kuantan Port during recent cases of paralytic shellfish poisoning (PSP) outbreaks showed extremely high in toxin content (32 937 fmol.cell-1) while the old culture of A. tamiyavanichii taken from Sebatu Malacca exhibited very low level of toxicity (0.4405 fmol.cell-1). There are many factors influencing toxicity properties of A. tamiyavanichii with highlights in nutrients deprivation and adaptation as well as bacterial influences for the old culture. Further justification is needed for both strains with consistency in culture medium in order to reason out the possibility of reduction in toxicity.